Fear learning and generalization in youth with early-stage transdiagnostic psychiatric symptoms and the impact of acute exercise - Jennen, Lise; Samaey, Celine; Qiao, Zhiling; Mazereel, Victor; Vansteelandt, Kristof; Vancampfort, Davy; van Winkel, Ruud (Frontiers in Psychiatry, 2025)
BackgroundAdolescence and early adulthood represent critical periods for the emergence of psychiatric symptoms, often spanning multiple symptom dimensions. Alterations in fear learning and generalization are implicated in anxiety-related disorders, yet research on these processes in youth with early-stage transdiagnostic psychiatric symptoms remains limited.MethodsThis study investigated fear learning and generalization in youth aged 16–24 years with transdiagnostic psychiatric symptoms (anxiety, depressive, and psychotic), as indexed by US expectancy ratings. Additionally, considering the modulatory impact of exercise on memory processes, we explored the effects of a 10-minute moderate-intensity exercise intervention using a randomized between-subject design.ResultsContrary to hypotheses, the symptom group did not show impaired threat–safety discrimination or overgeneralization of fear. However, they exhibited elevated overall threat expectancy during generalization, suggesting that a bias in threat expectancy could represent an early vulnerability in threat processing. Dimensional analyses point to subtle symptom-specific differences in generalization patterns, underscoring the importance of modeling continuous symptom severity alongside group-based comparisons. No significant effects of acute exercise on fear acquisition or generalization were observed.ConclusionThese findings highlight early alterations in threat processing in youth with early-stage psychiatric symptoms. Future research should investigate symptom-specific patterns in fear generalization, track their longitudinal development, and refine exercise interventions to effectively modulate fear processing.